Mga naisagawa sa Brgy. Loma, Maitim, Pangil at Talon, Minisipalidad ng Amadeo, Cavite pagsusuring pampamayanan - Elvambuena, Bryan F.; Obrero, Corina M.; Pacheco, Alyssa Camille D.; Peña, Reine Marie G.; Perea, Blessille Claire C.; Reyes, Clemarl Salvador M.; Reyes, Marie Antonia G.; Rillon, Angelica G.; Santos, Ma. Leoant B.; Tan, Joyce Camille L.; Yanoria, Alexander T.
Purpose: To establish baseline data on hypertension and to help in prioritizing health programs, this study aims to determine the prevalence of hypertension and its significant predictors in four rural areas in Amadeo, Cavite Methods: The study was conducted on January to March 2014 in Barangay Loma, Maitim I, Pangil and Talon in Amadeo, Cavite. A descriptive cross-sectional, correlational design was utilized. A list of households per barangay was obtained from the Sanitations Office of the Municipality of Amadeo. Systematic random sampling with replacement and Kish Grid method were utilized and 371 respondents who are ≥ 18 years old were selected for measurement of blood pressure, height, weight, and waist circumference, and interview, utilizing the WHO-adapted PHIL-PEN Risk Assessment Tool Results: 95.7% of respondents participated in the study. The prevalence of diagnosed hypertension is 21%. Among these, 68.42% have uncontrolled hypertension. Univariate logistic regression showed that familial history of hypertension (p=0.00), age 40-64 years (p=0.00) and ≥ 65 years (p=0.00), passive smoking (p=0.07), active smoking (p=0.00), being overweight (p=0.002), obesity (p=0.027), and central adiposity (p=0.00) are significantly associated with hypertension. Multivariate analysis revealed that familial history of hypertension (p=0.00), age 40-64 years (p=0.00) and ≥ 65 years (p=0.00), passive smoking (p=0.025), active smoking (p=0.001), and central adiposity (p=0.005) are significant predictors of hypertension in Amadeo, Cavite Conclusion: This study reveals the prevalence and predictors of hypertension in a previously understudied population. Prioritization and implementation of health programs addressing hypertension in these barangays may be based on the identified significant predictors of hypertension.